PERBANDINGAN EKSPRESI PROTEIN Bak DAN INDEKS APOPTOSIS SEL TROFOBLAS PADA KEHAMILAN PREEKLAMPSIA BERAT DAN KEHAMILAN NORMOTENSI - , Marihot Pasaribu ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Placental is a central and important focus on the pathogenesis of preeclampsia/eclampsia. Failure of trophoblast cell to the spiral arteries remodeling process due to excessive apoptosis causes uteroplacenter ischemia and damage of endothelial cells that give rise to clinical manifestasions of preeclampsia/ eclampsia. Excessive trophoblast apoptosis in preeclampsia/eclampsia mainly occurs through the intrinsic pathway in which expression of Bak protein increases mitochondrial membranes permeability of cytochrome C which further activated the caspase cascade and become involved in the process of cell death. Objective of study: To compare the expression of Bak protein and trophoblastic apoptotic index between severe preeclampsia and normotensive pregnancies. Methods: Cross sectional study which consist of 43 severe preeclampsia pregnancies and 38 normotensive pregnancies recruited between October 2011- March 2012. Trophoblastic cells Bak protein expression is measured by imunohistochemical staining technique and trophoblast apoptotic index quantification is examined by TUNEL assay. Results: There are significant differences of Bak protein expression in placental tissue of preeclampsia group (2.37Â±0.91, p=0.012) compared by normotensive group (1.92ï±0.59). There are significant differences of apoptotic index in placental tissue of preeclampsia group (0.44 0 Â± .26, p=0.00) compared by normotensive group (0.24ï±0.20). Conclusion: The Bak protein expression and the number of apoptotic cells in trophoblast tissue of preeclampsia complicated pregnancy were higher than normal pregnancy.